THE INFLUENCE OF ARABIC LEARNING ON THE STUDENTS' MOTIVATION IN MEMORIZING THE QUR'AN AT PONDOK PESANTREN IMAM ASY-SYATHIBY KABUPATEN GOWA - Siddik, Jaelani; Usman, Syahruddin; Munir, Munir (Jurnal Diskursus Islam, 2022)
This study aims to analyze the influence of Arabic language learning on the motivation to memorize the Qur'an students of the Imam Asy-Syathiby Islamic Boarding School, Gowa Regency. This type of research is field research, Ex-post facto, located at the Imam Asy-Syathiby Islamic Boarding School, Gowa Regency. The approach used in this study is the positivism approach. The population in this study covered high school students at the Imam Asy-Syathiby Islamic Boarding School, Gowa Regency, which amounted to 90 students, the sample in this study was 73. The data collection methods are observation, questionnaire, interview, and documentation, while the instruments used are observation guidelines, questionnaire grains, interview guidelines and documentation. Data processing and analysis techniques use descriptive statistical analysis and inferential statistics. The results showed that Arabic language learning at the Imam Asy-Syathiby Islamic Boarding School, Gowa Regency was relatively good. Based on the data analysis results from 73 respondents, there were five respondents with a very high classification, with a percentage of 6.8%, and 68 respondents with a high classification, with a percentage of 93.2%. The students' motivation for memorizing the Qur'an at Pondok Pesantren Imam As-Syathiby Kabupaten Gowa is relatively high. Based on the data analysis results from 73 respondents, there are 12 respondents with a very high classification, 16.4%, and 61 with a high classification, 83.6%. Based on the analysis results, learning Arabic affected the motivation to memorize the Qur'an for Pondok Pesantren Imam Asy-Syathiby, Gowa Regency students. That is shown from the analysis of the calculation of > of the table. From the calculation of 3,512 with a significance value of 0.001 <0.05, H0 is rejected, and Ha is accepted. With a termination coefficient of 14.8% rounded to 15%, the influence between variables in the low category, the remaining 85% is influenced by other variables that are not studied, including facilities and infrastructure, environmental factors, family, personality factors, intelligence levels and individual conditions.